Clinical biopsychosocial physiotherapy assessment of patients with chronic pain: The first step in pain neuroscience education. (3rd July 2016) - Wijma, Amarins J.; van Wilgen, C. Paul; Meeus, Mira; Nijs, Jo
ABSTRACT: Pain neuroscience education (PNE) is increasingly used as part of a physical therapy treatment in patients with chronic pain. A thorough clinical biopsychosocial assessment is recommended prior to PNE to allow proper explanation of the neurophysiology of pain and the biopsychosocial interactions in an interactive and patient-centered manner. However, without clear guidelines, clinicians are left wondering how a biopsychosocial assessment should be administered. Therefore, we provided a practical guide, based on scientific research and clinical experience, for the biopsychosocial assessment of patients with chronic pain in physiotherapy practice. The purpose of this article is to describe the use of the Pain – Somatic factors – Cognitive factors – Emotional factors – Behavioral factors – Social factors – Motivation – model (PSCEBSM-model) during the intake, as well as a pain analysis sheet. This model attempts to clearly establish what the dominant pain mechanism is (predominant nociceptive, neuropathic, or non-neuropathic central sensitization pain), as well as to assess the provoking and perpetuating biopsychosocial factors in patients with chronic pain. Using this approach allows the clinician to specifically classify patients and tailor the plan of care, including PNE, to individual patients.